Effects of Platelet Rich Plasma on Healing Rate of Long Bone Non-union Fractures: A Randomized Double-Blind Placebo Controlled Clinical Trial - Fariborz Ghaffarpasand; Mostafa Shahrezaei; Maryam Dehghankhalili (Bulletin of Emergency and Trauma, 2016)
Objective: To determine the effects of platelet rich plasma PRP on healing rates of long bone non-union fracture. Method: This was a randomized double-blind placebo controlled clinical trial being performed in a 12-month period. We included 75 adult (>18 years) patients suffering from long bone (Femur, Tibia, Humerus and Ulna) non-union fracture who were randomly assigned to receive 5mL PRP (n=37) or 5mL normal saline as placebo (n=38) in the site of fracture after intramedullary nailing or open reduction and internal fixation (ORIF) along with autologous bone graft. Patients were followed each 45 days till 9 months and were evaluated both clinically and radiologically in each visit. The healing rate, failure rate, incidence of infection, mal-union and limb shortening were recorded and compared between groups after 9 months of follow-up. Results: The healing rate was significantly higher in PRP group compared to placebo (81.1% vs. 55.3%; p=0.025). The limb shortening was significantly higher in those who received placebo (2.61±1.5 vs. 1.88±1.2mm; p=0.030). Injection of PRP was also associated with lower pain scores ( p=0.003) and shorter healing duration ( p=0.046). The surgical site infection ( p=0.262) and mal-union rate ( p=0.736) were comparable between groups. Conclusion: Application of PRP along with autologous bone graft in the site of non-union of long bone after intramedullary nailing or ORIF results in higher cure rate, shorter healing duration, lower limb shortening and less postoperative pain. Higher infection rate might be a complication of PRP application. Clinical Trial Registry: This trial is registered with the Iranian Clinical Trials Registry (IRCT201208262445N1; www.irct.ir).